Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2fo02146c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a cattle bone collagen peptide–calcium chelate by the ultrasound method and its structural characterization, stability analysis, and bioactivity on MC3T3-E1 cells

Abstract: This study was designed to prepare cattle bone-derived collagen peptides-calcium chelate by ultrasound method (CP-Ca-US), and its structural characterization, stability, and bioactivity on MC3T3-E1 cells were characterized. Single-factor experiments optimized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
(80 reference statements)
2
12
0
Order By: Relevance
“…Similar findings from an earlier study suggested that steam explosion might increase the release of protein hydrolysate from cow bone (Zhang et al ., 2020). The tight binding of the protein to hydroxyapatite that forms the bone structure may be destroyed by the steam explosion treatment, which may also cause the collagen superhelix to open up and produce more soluble protein (Zhang et al ., 2023a, 2023b). Only 56.49 ± 0.67% of the protein extracted from the chicken bone using the ultrasound‐assisted enzyme technique was recovered (Dong et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar findings from an earlier study suggested that steam explosion might increase the release of protein hydrolysate from cow bone (Zhang et al ., 2020). The tight binding of the protein to hydroxyapatite that forms the bone structure may be destroyed by the steam explosion treatment, which may also cause the collagen superhelix to open up and produce more soluble protein (Zhang et al ., 2023a, 2023b). Only 56.49 ± 0.67% of the protein extracted from the chicken bone using the ultrasound‐assisted enzyme technique was recovered (Dong et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Within 15–24 min, possibly because over time, the high‐pressure steam breaks down the collagen structure to produce a low‐molecular‐weight hydrolysate (major factor). In addition to the mechanical damage that the sudden release of steam causes to the bones of chickens, the accidental heated pressure that results from a steam explosion may also induce protein breakdown (Zhang et al ., 2023a, 2023b). The samples generated under the circumstances of 40% filling rate, 1.8 MPa pressure, and 12 min were ultimately chosen for the follow‐up study (calcium‐binding capacity and osteogenic activity) based on the aforementioned research findings and taking into consideration the recovery rate of chicken bone protein hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations